2022
DOI: 10.1186/s12877-022-03025-3
|View full text |Cite
|
Sign up to set email alerts
|

Determine the impact of a structured pharmacist-led medication review - a controlled intervention study to optimise medication safety for residents in long-term care facilities

Abstract: Background Medication reviews contribute to protecting long-term care (LTC) residents from drug related problems (DRPs). However, few controlled studies have examined the impact on patient-relevant outcomes so far. Objective We examined the impact of a one-time, pharmacist-led medication review on medication changes (primary endpoint) including discontinued medication, the number of chronic medications, hospital admissions, falls, and deaths (secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…Pharmacist-led interventions have the potential to reduce the incidence of MRP in older people living in nursing homes [ 24 , 25 ]. The observed overall rate of 78.0% of MRPs detected via routine review and resolved in response to the pharmacist’s alerts correlates well with data reported by Bitter et al in 2019 and Lexow et al in 2022 for geriatric residents in German long-term care facilities [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 85%
“…Pharmacist-led interventions have the potential to reduce the incidence of MRP in older people living in nursing homes [ 24 , 25 ]. The observed overall rate of 78.0% of MRPs detected via routine review and resolved in response to the pharmacist’s alerts correlates well with data reported by Bitter et al in 2019 and Lexow et al in 2022 for geriatric residents in German long-term care facilities [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 85%
“…However, the Drug Burden Index outcome significantly favoured the intervention. 18 Reduction in drug related problems is reported in another pharmacist led review intervention, 41 indicating there is potential for pharmacist led review to have some positive impacts for CH residents relating to side effects of some medicines. Further economic evaluation would be required to examine if this level of pharmacist input would be cost effective in practice.…”
Section: Discussionmentioning
confidence: 99%